Start hard, finish better: further evidence for the reversal of the RAE advantage. Issue 15 (2nd August 2016) - McCarthy, Neil; Collins, Dave; Court, David
ABSTRACT: The relative age effect (RAE) has been highlighted extensively within literature as influencing selection and identification within sports. However, this initial bias appears to not be systemic in some talent development systems. Accordingly, we report an investigation into the initial identification, selection and conversion of academy players from professional Rugby Union and Cricket at national level. Reflecting previous studies, data again demonstrated a reversal of RAE advantage whereby relatively young players from both sports were less likely to be selected into their respective national academy systems but were more likely to transition into senior national squads. On the basis of our observations, we further propose a psychological explanation for the mechanism of such a reversal, based on the influence of additional challenge experienced throughout the development journey. As such, we also highlight the need for further qualitative investigation to explore this phenomenon in greater depth.